Bibliometric of STEM education research in chemistry: Visualizing trends and scientific collaborations - Fatma Suryani Harahap; Eko Susetyarini; Elly Purwanti; Benny Sofyan Samosir; Syahruddin Aritonang (Universitas Muhammadiyah Malang, 2026)
Background-Science, Technology, Engineering, and Mathematics (STEM) education has become a key approach in 21st-century learning due to its role in enhancing higher-order thinking skills and interdisciplinary problem-solving abilities. Objectives-This study aims to systematically map the development and research directions of STEM education in the field of chemistry. Method-A bibliometric analysis integrated with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was employed to ensure a transparent and structured article selection process, including identification, screening, eligibility, and inclusion stages. Data were collected from the Scopus database using the keywords “STEM Education” and “Chemistry,” resulting in 132 articles that met the inclusion criteria. The data were analyzed using VOSviewer, Microsoft Excel, and Publish or Perish (PoP) to examine publication trends, international collaboration networks, author productivity, and dominant research themes. Results-The results indicate a significant increase in publications since 2016, with a peak in 2024, reflecting growing global interest in STEM-based chemistry education. The dominant research themes include active learning, systems thinking, virtual learning, and project-based learning, indicating a shift from content-oriented teaching toward the development of scientific and creative competencies. In addition, international collaboration highlights the central role of the United States, Malaysia, and Germany, while contributions from Indonesia and Southeast Asia continue to grow. Conclusion-This study demonstrates that STEM education in chemistry has evolved into a dynamic and globally connected research field. The findings provide strategic insights for future research development, educational policy formulation, and the strengthening of international collaboration in STEM-based chemistry education.